Systems medicine, personalized health and therapy. (September 2015) - Siest, Gérard; Auffray, Charles; Taniguchi, Naoyuki; Ingelman-Sundberg, Magnus; Murray, Helena; Visvikis-Siest, Sophie; Ansari, Marc; Marc, Janja; Jacobs, Peter; Meyer, Urs; Van Schaik, Ron HN; Müller, Mathias M; et al.
The 7th Santorini Conference was held in Santorini, Greece, and brought together 200 participants from 40 countries in several continents, including Europe, USA but also Japan, Korea, Brazil and South Africa. The attendees had the opportunity to: listen to 60 oral presentations; participate in two lunch symposia; look at 103 posters, which were divided in two groups ('systems medicine and environment' and 'pharmacogenomics and cancer') and attend a dedicated exhibition with six companies. The meeting was organized by the Institut National de la Santé et de la Recherche Médicale (INSERM) U1122; IGE-PCV and by 'Biologie Prospective' with the collaboration of the European Society of Pharmacogenomics and Theranostics (ESPT), under the auspices of international organizations (e.g., International Federation of Clinical Chemistry and Laboratory medicine [IFCC], European Federation of Clinical Chemistry and Laboratory Medicine [EFLM], European Diagnostic Manufacturers Association [EDMA], Federation of European Pharmacological Societies [EPHAR], European Science Foundation [ESF]). The 3 days of the conference stimulated intensive discussions on systems biology and the influence of omics technologies on personalized health. Sixty speakers were invited or selected from early abstracts and gave presentations on the following topics: From systems biology to systems medicine/pharmacology; Omics/translating pharmacogenomics/proteomic biomarkers/metabolomics; Human nutrition and health/personalized medicine. We are summarizing here the main topics and presentations, according to the successive sessions.